2008
DOI: 10.2140/pjm.2008.235.323
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic volume functional on almost complex 6-manifolds and nearly Kähler geometry

Abstract: Let (M, I) be an almost complex 6-manifold. The obstruction to integrability of the almost complex structure (the so-called Nijenhuis tensor) N : Λ 0,1 (M ) −→ Λ 2,0 (M ) maps a 3-dimensional bundle to a 3-dimensional one. We say that Nijenhuis tensor is non-degenerate if it is an isomorphism. An almost complex manifold (M, I) is called nearly Kähler if it admits a Hermitian form ω such that ∇(ω) is totally antisymmetric, ∇ being the Levi-Civita connection. We show that a nearly Kähler metric on a given almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…For a history of this notion, a number of equivalent definitions and a bibliography of current work in this field, we refer the reader to Mororianu, Nagy and Semmelmann [23] and our paper [31].…”
Section: Nearly Kähler 6-manifoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a history of this notion, a number of equivalent definitions and a bibliography of current work in this field, we refer the reader to Mororianu, Nagy and Semmelmann [23] and our paper [31].…”
Section: Nearly Kähler 6-manifoldsmentioning
confidence: 99%
“…In [31] we showed that, unless a nearly Kähler manifold M is locally isometric to a 6-sphere, the almost complex structure on M is uniquely determined by the metric. Friedrich [9] proved this result for S 6 as well.…”
Section: Nearly Kähler Manifolds In Geometry and Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], a characterization of compact locally conformal parallel G 2 -manifolds as fiber bundles over S 1 with compact nearly Kähler fiber was obtained (see also [7]). …”
Section: Introductionmentioning
confidence: 99%
“…If there exists an almost complex structure J on M such that (M, g, J) is nearly Khler (non Khlerian) then it is unique. Moreover, in this case, J is invariant by the isometry group of g. This can be proved using the spinors (by [27], a 6-dimensional Riemannian manifold admits a nearly Khler structure if and only if it carries a real Killing spinor): see [8] proposition 2.4 and the reference therein [5], proposition 1, p126, or by a "cone argument" (see below) as in [43], proposition 4.7.…”
mentioning
confidence: 99%